WAR, TRAUMA, AND BRINGING THEM ALL HOME … - Brooke, Roger (PINS-Psychology in Society, 2025)
Tick, Ed (2005) War and the soul. Wheaton, Illinois: Quest Books. ISBN 978-0-8356-0831-2. Pages 341. Ed Tick is a psychotherapist who has been working with veterans for some 30 years. He is also an authority on Greek healing rituals and warrior cultures, including the Greeks and Romans, Zulus, Celts, Norse, and especially, the American Plains Indians. He is an ordained interfaith minister and a recognised healer by traditional Native Americans on the northern plains. Tick writes with a deep understanding of the calling to be a warrior and love for the men and women who respond to that call, even as he has been a peace activist all his adult life. This tension – love for the warrior and peace activism – is one of the moving strengths of the book.